Växthus på Vaksala Eke - Berg, Karin; Brené, Erik; Dahlström, Lukas; Lanner, Victor; Larsson, Emanuel; Ljungqvist Baldesi, Raffaello; Majid, Safwat; Söderberg, Jonas (2018)
This project has been carried out on the behalf of IHUS and the aim was to ﬁnd a solution to a greenhouse with an associated café on Vaksala Eke just north of Uppsala. This complex is intended to be self-suﬃcient on heat, electric power and crops. In the project we have created a greenhouse that fully supplies the café with crops during the summer, while during the winter the greenhouse only provides 8-16% of the café’s demand of crops. Six diﬀerent scenarios were created to cover the heat demand of the greenhouse and the café. The following scenarios for the heat supply were considered: ground heat; solar thermal energy and ground heat; geothermal energy; solar thermal energy and geothermal energy; bioenergy; solar thermal energy and bioenergy. These six scenarios were compared to one another to obtain the most proﬁtable system. The results showed that the scenario with the shortest payback period for heat generation, is the ground heat scenario. Photovoltaic solar panels is the only source of electric power examined for the small-scale operation on Vaksala Eke. All the scenarios, except for the scenarios with bioenergy, were fully self-suﬃcient on heat, on the other hand all the scenarios were self-suﬃcient on electricity over a year.